Assessing mobility in sustainable urban regeneration. The GBC Quartieri application to Le Albere neighbourhood in Trento - Mazzola, Elena; Bove, Alessandro (TeMA - Journal of Land Use, Mobility and Environment, 2024)
In order to minimise the negative impacts of new districts, mobility analysis plays a crucial role. Indeed, urban expansion may lead to increased car use to access basic services. Establishing interconnections between novel localities, parking spaces, public transportation routes, limiting the heat island phenomenon and instituting renewable energy sources are indispensable for realising sustainable design. This approach may mitigate the adverse impacts of informal urban expansion and foster condensed, pedestrian-oriented neighbourhoods that encourage cycling and walking. In this context, international protocols can provide valuable guidance during the planning and upkeep phases by furnishing analysis and design recommendations. In this paper, starting with an analysis of the GBC Quartieri energy and environmental sustainability protocol on an urban scale, a method for evaluating the protocol's responses to known mobility-related critical issues was prepared and used to evaluate the case study Trento Le Albere project. This showed that almost 50 per cent of the internal credits and prerequisites are focused on mobility, including the smart location of the new neighbourhood and the implementation of bicycle mobility, interchange points and shaded streets. These solutions were evaluated based on their relationships with critical mobility issues, providing a comprehensive solution that focuses chiefly on the connection system, accessibility and usability performance, control, and climatic impact.